The Effect of Selected Exercises on the Motor Development of Overweight and Obese Iraqi Children Aged 8 to 9 Years: The Moderating Role of Gender - Bayyat Mohammad, Firas; Abdi, Hassan; Algnabe , Akram Hoossein; Serjooei, Zahra; Faraeen, Maryam (Health Nexus, 2025)
The objective of this study was to examine the effect of selected exercises on the motor development of overweight and obese Iraqi children aged 8 to 9 years, considering the moderating role of gender. This research employed a quasi-experimental design with a pre-test and post-test structure, including both control and experimental groups. The statistical population consisted of overweight and obese children aged 8 to 9 years in the city of Baghdad. The sample included 40 children from Baghdad, selected voluntarily and based on inclusion and exclusion criteria using convenience sampling. To measure motor development, the short form of the second edition of the Bruininks-Oseretsky Test of Motor Proficiency was utilized. The selected exercises were derived from the SPARK training protocol. Data analysis was conducted using factorial analysis of variance (ANOVA) and univariate analysis of covariance (ANCOVA). All statistical procedures were performed using SPSS version 25, with a significance level set at p < 0.05. The results indicated a significant difference in fine motor skills between the experimental and control groups following the implementation of the selected exercises (p < 0.05). However, the effect of gender was not significant (p > 0.05). Furthermore, the mean scores of the experimental group in both gross motor skills and fine motor skills were significantly higher than those of the control group (p < 0.001). The effect of gender was significant for gross motor skills (p < 0.05) but not for fine motor skills (p > 0.05). The findings suggest that the selected exercises effectively enhance the fine motor skills of overweight and obese Iraqi children aged 8 to 9 years, with no significant difference between boys and girls. However, the effectiveness of the selected exercises on gross motor skills differs between overweight and obese boys and girls in this age group.